Aprendizagem histórica através das pinturas de Moacyr Freitas : os usos e apropriações de imagens no ensino de história regional - Morais, Edenilson José de (2019)
This dissertation had as main objective to investigate the use of iconography in the teaching of Regional History, particularly using the historical pictures produced by the painter Cuiabano Moacyr Freitas and present in the didactic book History of Mato Grosso: from the ancestry to the present days, that were constituted in our object of study. It was intended to analyze the way these images incorporated the official speeches, produced by the Historical and Geographical Institute of Mato Grosso. It was tried to verify that writers and historians influenced in the elaboration of the screens and that intentionality can be evidenced when observing these historical pictures. It was sought to emphasize in what ways the teacher of History of Basic Education can make use of such images in the classroom trying to understand them and interpret them critically together with the students. For the development of this work, the works of Moacyr Freitas, painter and writer, member of the IHGMT, historical institution that contributed to the construction of a Mato Grosso regional identity and to the legitimation of an official History of positivist orientation were used.